Redshifting the Study of Cold Brown Dwarfs and Exoplanets: The Mid-infrared Wavelength Region as an Indicator of Surface Gravity and Mass - S. K. Leggett; Pascal Tremblin (The Astrophysical Journal)
JWST is opening many avenues for exploration. For cold brown dwarfs and exoplanets, JWST has opened the door to the mid-infrared wavelength region, where such objects emit significant energy. For the first time, astronomers have access to mid-infrared spectroscopy for objects colder than 600 K. The first spectra appear to validate the model suite known as ATMO 2020++: atmospheres that include disequilibrium chemistry and have a nonadiabatic pressure–temperature relationship. Preliminary fits to JWST spectroscopy of Y dwarfs show that the slope of the energy distribution from λ ≈ 4.5 μ m to λ ≈ 10 μ m is very sensitive to gravity. We explore this phenomenon using PH _3 -free ATMO 2020++ models and updated Wide-field Infrared Survey Explorer W2−W3 colors. We find that an absolute 4.5 μ m flux measurement constrains temperature, and the ratio of the 4.5 μ m flux to the 10–15 μ m flux is sensitive to gravity and less sensitive to metallicity. We identify 10 T dwarfs with red W2−W3 colors that are likely to be very-low-gravity, young, few-Jupiter-mass objects; one of these is the previously known COCONUTS-2b. The unusual Y dwarf WISEPA J182831.08+265037.8 is blue in W2−W3, and we find that the 4–18 μ m JWST spectrum is well reproduced if the system is a pair of high-gravity 400 K dwarfs. Recently published JWST colors and luminosity-based effective temperatures for late-T and -Y dwarfs further corroborate the ATMO 2020++ models, demonstrating the potential for significant improvement in our understanding of cold, very-low-mass bodies in the solar neighborhood.